Caribbean Livestock: improving health and nutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
seminar held in Antigua in November 1990. The meeting, which was organized jointly by CTA and the Caribbean Agricultural Research and Development Institute (CARDI), focused on the control of two tick-associated diseases, cowdriosis and dermatophilosis